Strategi Kebahasaan dalam Mengungkapkan Duka pada Film Di Tinggal Meninggal sutradara Kristo Immanuel: Analisis Wacana Kritis Model Norman Fairclough - Mahmudah; Lestari, Adhe Utami; Ridwan (Universitas Insan Budi Utomo, 2026)
This study seeks to describe the linguistic strategies used to express grief in the film ‘Di Tinggal Meninggal’, directed by Kristo Immanuel, through Norman Fairclough’s model of Critical Discourse Analysis. The study employs a descriptive qualitative method, utilizing data collection techniques such as documentation and the transcription of dialogues that capture expressions of grief in the film. The data were analyzed based on Fairclough’s three dimensions of critical discourse analysis: the text dimension (linguistic analysis), discursive practices (the processes of text production and consumption), and social practices (the socio-cultural context underpinning the discourse). The research findings indicate that linguistic strategies for expressing grief are manifested through the selection of emotional vocabulary, metaphors of loss, repetitive sentence structures, the use of pauses and silence, and forms of implicature that reflect the psychological distress of the characters. At the level of discursive practices, the representation of grief is shaped through natural and contextual dialogues, while at the level of social practices, the discourse of grief reflects social realities regarding family relationships, loss, and emotional stigma within society. Thus, this film not only portrays grief as a personal experience but also as a social construction influenced by power relations and cultural values